Transition from Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs): Blueprint of Bangladesh for Implementing the Sustainable Development Goals (SDGs) 2030 - Ashraf, Musfiqa; Ullah, Lokiat; Shuvro, Muqsuda Ashraf; Salma, Umme (Medicine Today, 2019)
Introduction: The Sustainable Development Goals 2030, titled “Transforming Our World: The 2030 Agenda for Sustainable Development” with 17 goals and 169 targets (including 43 means of implementation) were adopted at the United Nations in September 2015. The Seventh Five Year Plan of Bangladesh (SFYP), “Accelerating Growth, Empowering Every Citizen” for the years 2016-2020, produced by General Economics Division, Planning Commission, can be regarded as the blue print for the early critical phase of Sustainable Development Goals (SDG) implementation. Materials & Methods: This Review Article was prepared based on updated International Newsletter, Journal and Data from Bangladesh Government Planning Commission. Discussion: Challenges of Sustainable Development Goals (SDGs) and 7th Plan include resource mobilization, tapping population momentum, managing unplanned urbanization, natural disasters and climate change, utilization of resources, skill development and quality education, improving competitiveness, governance, taming inequality and regional disparity. Bangladesh prepared its own post-2015 Development Agenda and contributed to the international discourse through UN. Conclusion: The General Economics Division (GED) of the Planning Commission, based on a consultative process initiated in 2013, goals and targets were developed in the context of Bangladesh. Through this process, 11 goals along with 58 targets with corresponding 241 measurable indicators were proposed. Civil society in Bangladesh also produced what is described as “a people-centred, equitable, inclusive, and sustainable Post-2015 Development Agenda.” It came up with 13 Goals,50 Targets and 199 Indicators. Medicine Today 2019 Vol.31(1): 46-59